Thermophysical Property Measurements with the Finite Bar - Christoph Ellenrieder; André Kaufmann; Benedikt Reick; Marcus Geimer (Applied Sciences, 2023)
Knowledge of thermophysical properties of materials is important in the design process to meet the ambitious targets with respect to reliability and performance of many modern machinery. In this paper a simple method for the measurements of thermophysical material properties is presented. A bar of the sample material is heated at one end by a constant heat source and temperature sensors on or in the sample material at different locations record the temperature response. In the limit of small Fourier-Numbers the temperature will not rise at the adiabatic end and the comparison to the theoretical curve allows to extract thermophysical data. In the case of large Fourier-Numbers a quasi steady temperature profile in the bar allows to extract all relevant thermophysical properties simultaneously. Apart from the theory some measurement results are presented and the errors due to diabatic boundary conditions are discussed.